2006
DOI: 10.5424/sjar/2006044-210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature on the flavour of citrus fruit

Abstract: This paper reports the effect of different storage temperatures (5, 15, 20 and 25 deg C) on the flavour of cv. Valencia Late Frost oranges stored for up to one month (following a pre-experimental two month storage period at 5 deg C). Samples were instrumentally analysed every week for titratable acidity, soluble solid content, maturity index, and ethanol and acetaldehyde contents. In addition, four sensory attributes were assessed by 20 taste panellists (this work formed part of their training): acidity, matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
1
13
0
4
Order By: Relevance
“…However, the weight loss is mainly associated with temperature, relative humidity and evaporation (Montgomery, 1997;Molnar, 1995;Scalzo et al, 2003;Dixon et al, 2004 andLuning &Marcelis, 2006). The studies carried out in the past (Marcilla et al, 2006;Wandel & Bugget, 1997;Vashishtha, 1998) have reported that temperature and storage duration affect the vitamin C content of fruit considerably (Kadzere et al, 2006). The storage temperature and duration have linear association in relation to changes quality and shelf life of fruits (Lee & Kader, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, the weight loss is mainly associated with temperature, relative humidity and evaporation (Montgomery, 1997;Molnar, 1995;Scalzo et al, 2003;Dixon et al, 2004 andLuning &Marcelis, 2006). The studies carried out in the past (Marcilla et al, 2006;Wandel & Bugget, 1997;Vashishtha, 1998) have reported that temperature and storage duration affect the vitamin C content of fruit considerably (Kadzere et al, 2006). The storage temperature and duration have linear association in relation to changes quality and shelf life of fruits (Lee & Kader, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Distribution of the temperature and relative humidity in a cold store was important because these factors affect quality of stored products. Many studies on the effect of storage temperature on quality and storage life of fruits have been carried out which indicate that temperature plays an important role on quality of fruits after harvest (Marcilla et al 2006). The Objective of this study was to analyse air temperature and velocity distribution in an experimental cold store full loaded apples by using both experimental and numerical (CFD) methods.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques are adopted to minimize post-harvest changes in fruit, like temperature management which extends the shelf life of fruits (Aulakh, 2004;Lee & Kader, 2000) by regulating physiological and biochemical processes. But at the same time, lower temperatures may cause chilling damage and higher ones can reduce the storage life of the product (Biolatto et al, 2005;Dixon et al, 2004;Marcilla et al, 2006;Pailly et al, 2004;Tembo et al, 2008;Widayat et al, 2003). The guava is normally marketed as its processed products such as puree, paste, cheese, dehydrated products, jam, jelly, juice, pectin, spread, yoghurt, syrup, squash and canned slices in syrup or nectar (Jagtiani et al, 1988).…”
Section: Introductionmentioning
confidence: 99%